(3GdJUQjM HeVehf GdJhVjMs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s; (3LeGd GdOjf CHh eMeO YHO Gddg jhSa Hf gTGes
(3ChdgG (B:s
(3Chd GdehLhO efg hcGf Pdc GdGSe hGdJPcjQ Ch ZjQgeG ef GdJCfjK hGdJKfjI hGdLeY s
(3BNQgG (B:s
(3aGf bdJ MHW GdMGA hGLH GdJQcjH Cf LYdJgG dNOeI GdhGMOI Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs